2020
DOI: 10.36740/wlek202012108
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio as Predictors of Coronary Microcirculatory Disease Occurrence and Outcome in Patients With Chronic Coronary Syndrome and No Significant Coronary Artery Stenosis

Abstract: Introduction: Index of microcirculatory resistance assessment is an invasive method of measuring coronary microcirculation function. Association between impaired microcirculatory function and higher rate of cardiovascular events was proven. Neutrophil-lymphocyte ratio and platelet-lymphocyte ratio seem to be a promising parameters to predict coronary microcirculatory disease in patients with chronic coronary syndrome. The aim: To determine neutrophil-lymphocyte ratio and platelet-lymphocyte ratio levels in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…According to recent studies, NLR is a powerful systemic inflammatory indicator associated with the prevalence and severity of CAD [10,11]. Our study showed higher NLR levels in CAD, including CCS and particularly AMI.…”
Section: Discussionsupporting
confidence: 65%
“…According to recent studies, NLR is a powerful systemic inflammatory indicator associated with the prevalence and severity of CAD [10,11]. Our study showed higher NLR levels in CAD, including CCS and particularly AMI.…”
Section: Discussionsupporting
confidence: 65%
“…The prognostic importance of complete blood count parameters (neutrophil/ lymphocyte ratio, platelet/lymphocyte ratio, mean platelet volume, and neutrophil/monocyte) in coronary artery disease (CAD) has been demonstrated in many studies. [10][11][12] Hemoglobin (Hb) is generally used to define anemia along with other parameters such as hematocrit. However, recent works suggest that Hb is also a predictor of hospital admission of subjects with chronic diseases.…”
Section: Study Populationmentioning
confidence: 99%